GAMELAN SALONDING MASUK HOTEL Studi Kasus: PERKEMBANGAN GAMELAN SALONDING DI DESA TENGANAN PEGRINGSINGAN, KECAMATAN MANGGIS, KABUPATEN KARANGASEM - I Wayan Sudiarsa (WIDYANATYA, 2021)
The Salonding Gamelan is one of the many Balinese gamelan groups which until now its existence still shows a close relationship that occurs between ritual and art. Gamelan Salonding is one type of Balinese gamelan that belongs to the old gamelan group and is thought to have developed before the XV century, namely during the Bali Aga / Old Age . However, in the course of its history of existence, it seems that now the Salonding gamelan not only appears to exist as a sacred art, but has also been developed for non-sacred interests.This was observed fro the development of the Salonding Gamelan outside the village of Tenganan Pegringsingan. As with the secularization of various types of Balinese performing arts, the Salonding gamelan, which initially only had a sacred function, also did not escape this. The secularization of the Salonding gamelan is basically due to the influence of rationalization, modernization and commercialization as an excess of changes in the social system of society and the development of the tourism industry in Bali.